d-Pinitol promotes tau dephosphorylation through a cyclin-dependent kinase 5 regulation mechanism: A new potential approach for tauopathies? - Medina-Vera, Dina; Navarro, Juan Antonio; Rivera-González, Patricia (WILEY, 2022)
Background and Purpose Recent evidence links brain insulin resistance with neurodegenerative diseases, where hyperphosphorylated tau protein contributes to neuronal cell death. In the present study, we aimed to evaluate if d-pinitol inositol, which acts as an insulin sensitizer, affects the phosphorylation status of tau protein. Experimental Approach We studied the pharmacological effect of d-pinitol on insulin signalling and tau phosphorylation in the hippocampus of Wistar and Zucker rats. To this end, we evaluated by western blotting the Akt pathway and its downstream proteins as being one of the main insulin-mediator pathways. Also, we explored the functional status of additional kinases phosphorylating tau, including PKA, ERK1/2, AMPK and CDK5. We utilized the 3xTg mouse model as a control for tauopathy, since it carries tau mutations that promote phosphorylation and aggregation. Key Results Surprisingly, we discovered that oral d-pinitol treatment lowered tau phosphorylation significantly, but not through the expected kinase GSK-3 regulation. An extensive search for additional kinases phosphorylating tau revealed that this effect was mediated through a mechanism dependent on the reduction of the activity of the CDK5, affecting both its p35 and p25 subunits. This effect disappeared in leptin-deficient Zucker rats, uncovering that the association of leptin deficiency, obesity, dyslipidaemia and hyperinsulinaemia abrogates d-pinitol actions on tau phosphorylation. The 3xTg mice confirmed d-pinitol effectiveness in a genetic AD-tauopathy.
Keywords: Insulina; Akt; CDK5; D-pinitol; IInsulin; Tau phosphorylation; Tauopathy